Privacy Preserving in Opportunistic Routing for Wireless Sensor Networks - Rani, Diksha; Kumar, Yogesh (International Journal of Computer Sciences and Engineering, 2019)
There are large numbers of sensor nodes deployed within wireless sensor networks. These nodes contain batteries of extremely small size. Moreover, these nodes are generally deployed at distant locations. Therefore, replacing these batteries is not a good option. Hence, in WSN, the efficient use of battery is a main challenge. The base paper proposes a novel routing algorithm called opportunistic routing. This algorithm is used to route data packets in wireless sensor networks. The source node stores the data on the intermediate node in this sort of routing. The source node will move close to the sink node or base station. This node delivers data to the sink node. The priority is assigned to the data stored on the intermediate node. The data with higher priority is transmitted first to the sink node. A simulation tool named NS2 is used for the simulation of proposed algorithm. It has been analyzed that proposed algorithm gives better performance in terms of different performance metrics.